ANALISIS YURIDIS KEPEMILIKAN HAK ATAS TANAH YANG DIKUASAI OLEH MENANTU PEREMPUAN (PUTUSAN MA NOMOR 1648 K/PDT/2015) - YUSUF TAMAMI (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Muhammad Yamin, SH, MS, CN2. Prof. Dr. Saidin, SH, MHum3. Dr. Idha Aprilyana Sembiring, SH, MHum The land that has been registered must have authentic evidence in written form. This authentic evidence is made in form of land title certificate. With the issuance of land title certificate, the State juridical acknowledges the ownership of a piece of land to those whose names are written in its certificate. Thus, the land title ownership cannot be claimed by any other parties. By the enactment of the Agrarian Act, the government provides as fair rights as possible for all Indonesian people concerning land problems; however, the land has to have social functions to be useful for social welfare for the owner and the society. The research problems are 1). How the legality of the title ownership over the land that is occupied by a daughter in law is, according to the law implemented in Indonesia, 2) How the legal protection for the land title holder over the certified land that is occupied by a daughter in law and how the legal consequences are, and 3) How the legal consideration of the judge is, in the Verdict of the Supreme Court No. 1648 K/Pdt/2015.This research employs normative juridical method with descriptive analysis. The data were collected through library research and field research, by conducting document study and guided interviews. They were then analyzed qualitatively. The conclusion is drawn deductively by drawing general things to specific ones.Keywords :Ownership, Land Title, Daughter in Law